Preliminary safety and effectiveness of psilocybin-assisted therapy in adults with fibromyalgia: an open-label pilot clinical trial - Aday, Jacob S.; McAfee, Jenna; Conroy, Deirdre A.; Hosanagar, Avinash; Tarnal, Vijay; Weston, Cody; Scott, Katherine; Horowitz, Dana; Geller, Jamarie; Harte, Steven E.; Pouyan, Niloufar; Glynos, Nicolas G.; et al. (Frontiers in Pain Research, 2025)
IntroductionFibromyalgia (FM) is the prototypical nociplastic pain condition, characterized by widespread pain and issues with cognition, mood, and sleep. Currently, there are limited treatment options available that effectively treat FM symptoms. Psilocybin-assisted therapy (PAT) is an emerging combined drug-therapy intervention, but no studies to-date have investigated PAT for FM.MethodsHere, we report findings from an open-label, pilot clinical trial of PAT for FM (N = 5). In conjunction with psychotherapy (two preparatory, four integration sessions), participants received two doses of oral psilocybin (15 mg and 25 mg) delivered two weeks apart.ResultsRegarding safety (primary outcome), there were transient elevations of blood pressure or heart rate during dosing which normalized by the end of treatment, with no serious adverse events. Four of five participants reported transient headaches following dosing. Compared to baseline, participants reported clinically meaningful improvements in the following secondary outcomes one month following their second psilocybin dose (reported as Cohen's d): pain severity [d = −2.1, 95% CI(−3.7 to −0.49)], pain interference [d = −1.8, 95% CI (−3.27 to −0.24)], and sleep disturbance [d = −2.5, 95% CI (−4.21 to −0.75)]. Using the Patient Global Impression of Change, one participant reported their symptoms “very much improved,” two reported “much improved,” and two reported “minimally improved.” We stopped recruitment early because of concerns about generalizability and changes in FDA guidance for psychedelic clinical trials that occurred data collection.DiscussionThis small open-label trial preliminarily supports that PAT is well-tolerated by people with FM, establishing a basis for larger randomized controlled trials.Clinical Trial RegistrationClinicalTrials.gov, identifier, (NCT05128162).